Web Accessibility in Africa: A Study of Three African Domains - (:unkn) unknown (My University, 2013)
Being the most used method for dissemination of information, especially for public services, it is of paramount importance that the Web is made accessible as to allow all its users to access the content of its pages.In this paper, we evaluated 2250 Governmental Web pages from each one of three different African countries (i.e., Angola, Mozambique and South Africa). This report compares the accessibility quality and the level of structural complexity of these African countries government’s Web pages. We found that hand coded pages tend to have larger number of HTML elements and also to present higher number of accessibility problems. Finally, it suggests some recommendations to repair the most common problems in these pages.
Keywords: African Research